2016
DOI: 10.1016/j.radonc.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Modelling second malignancy risks from low dose rate and high dose rate brachytherapy as monotherapy for localised prostate cancer

Abstract: Article:Murray, L orcid.org/0000-0003-0658-6455, Mason, J, Henry, AM orcid.org/0000-0002-5379-6618 et al. (4 more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In contrast both LDR and HDR brachytherapy monotherapy result in low estimated risks of radiation-induced second malignancy. In particular excess absolute risks for LDR brachytherapy of 0.71 per 10,000 person-years (PY) and 0.84 per 10,000 PY respectively for rectal and bladder cancer have been estimated [61]. The corresponding rates for HDR brachytherapy were 0.74 and 1.62 per 10,000 PY respectively.…”
Section: Second Malignancy After Prostate Brachytherapymentioning
confidence: 99%
“…In contrast both LDR and HDR brachytherapy monotherapy result in low estimated risks of radiation-induced second malignancy. In particular excess absolute risks for LDR brachytherapy of 0.71 per 10,000 person-years (PY) and 0.84 per 10,000 PY respectively for rectal and bladder cancer have been estimated [61]. The corresponding rates for HDR brachytherapy were 0.74 and 1.62 per 10,000 PY respectively.…”
Section: Second Malignancy After Prostate Brachytherapymentioning
confidence: 99%
“…A possible explanation was that Aksnessaether et al (39) used high dose rate BT for prostate cancer treatment, which increased the aforementioned risk. High dose radiotherapy caused a higher risk of secondary bladder cancer than low dose radiotherapy (40). In the rst decade of this century, intensity-modulated radiotherapy (IMRT) became popular because it reduced the radiationrelated toxicity and meanwhile improve survival (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, some have even reported that the risk of developing a secondary cancer was lower with either low dose or high dose rate BT alone when compared to any EBRT technique 30. When further focused on the dose of BT, Murray et al40 revealed that PCa patients who received a low dose rate of BT resulted in lower BLCa risks than high dose rate. Taken together, it is likely to recommend younger and healthier patients who did not accept RP treatment for reasons to select BT.…”
Section: Discussionmentioning
confidence: 99%